2019
DOI: 10.1016/j.ebiom.2019.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Dual lysosomal-mitochondrial targeting by antihistamines to eradicate leukaemic cells

Abstract: BackgroundDespite great efforts to identify druggable molecular targets for AML, there remains an unmet need for more effective therapies.MethodsAn in silico screening was performed using Connectivity Maps to identify FDA-approved drugs that may revert an early leukaemic transformation gene signature. Hit compounds were validated in AML cell lines. Cytotoxic effects were assessed both in primary AML patient samples and healthy donor blood cells. Xenotransplantation assays were undertaken to determine the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 72 publications
(93 reference statements)
3
31
0
Order By: Relevance
“…Then, the lower levels of HRH1 observed in AML and MDS could be related to the low levels of HRH1 seen in HSCs and non‐myeloid blood cells, as previously reported (Figure 1A). 2 On the other hand, pharmacological modulation or CRISPR‐mediated KD of HRH1 did not induce significant effects on chemosensitivity or basal differentiation state, while histamine induced only a moderate reduction in clonogenic capacity, thus precluding the therapeutic potential of HRH1 targeting in myeloid malignancies and further supporting a minor role of HRH1, in line with previous results 5 . Despite the lack of effects of HRH1 modulation in leukaemogenesis, our results establish a role for HRH1 in myeloid differentiation.…”
Section: Figuresupporting
confidence: 89%
See 2 more Smart Citations
“…Then, the lower levels of HRH1 observed in AML and MDS could be related to the low levels of HRH1 seen in HSCs and non‐myeloid blood cells, as previously reported (Figure 1A). 2 On the other hand, pharmacological modulation or CRISPR‐mediated KD of HRH1 did not induce significant effects on chemosensitivity or basal differentiation state, while histamine induced only a moderate reduction in clonogenic capacity, thus precluding the therapeutic potential of HRH1 targeting in myeloid malignancies and further supporting a minor role of HRH1, in line with previous results 5 . Despite the lack of effects of HRH1 modulation in leukaemogenesis, our results establish a role for HRH1 in myeloid differentiation.…”
Section: Figuresupporting
confidence: 89%
“…Histamine is a pleiotropic biogenic amine acting through four different histamine receptors (HRH1 to HRH4) belonging to the G protein‐coupled receptor superfamily. Although most of the proposed effects of histamine on myeloid differentiation are mediated by HRH2, 2,3 the expression of HRH1 in AML cell lines has recently been reported 5 . Nevertheless, no role for HRH1 in leukaemia has been identified.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Cationic amphiphilic drugs (CAD), including loratadine and ebastine, can exert their effect through accumulation in both mitochondria and lysosomes [ 214 ]. However, the inhibition of autophagy/mitophagy in certain steps produces increased drug sensitivity.…”
Section: Csc Resistance In Mitophagymentioning
confidence: 99%
“…Using an in silico screening assay to assess the cytotoxic effects of FDA-approved drugs for the treatment of AML, Cornet-Masana and colleagues [3] identified a subset of antihistamines with distinct physicochemical properties that selectively killed AML cell lines and primary patient samples. Starting with gene expression profiling experiments involving an MLL-AF9 induced AML model, the authors found HRH1 inverse agonists had properties that reversed the transformation gene signature.…”
mentioning
confidence: 99%